Unravelling the pleiotropic role of the MceG ATPase in Mycobacterium smegmatis. (11th May 2017) - García‐Fernández, Julia; Papavinasasundaram, Kadamba; Galán, Beatriz; Sassetti, Christopher M.; García, José L.
Summary: The Mce systems are complex ABC transporters that are encoded by different numbers of homologous operons in Actinobacteria. While the four Mce systems of Mycobacterium tuberculosis are all energized by a single ATPase, MceG, each system appears to import different fatty acids or sterols. To explore if this behaviour can be extended to saprophytic mycobacteria, whose more complex genomes encode more Mce systems, we have identified and characterized the MceG orthologue of Mycobacterium smegmatis . This bacterium relies on MceG to energize its six Mce systems that contribute to a variety of cellular functions including sterol uptake and cell envelope maintenance. In the absence of MceG, M. smegmatis was not able to utilize cholesterol or phytosterols as carbon sources implying that this ATPase is necessary to energize the Mce4‐sterol transport system. Other phenotypic alterations observed in the ΔMceG mutant, such as cell envelope modifications, suggest a pleiotropic functionality of the Mce systems that are particularly important for stress responses. Several ΔMceG phenotypes were recapitulated in a strain lacking only the unique C‐terminal region of MceG, suggesting an important functional or regulatory function for this domain.